Mapping of predictors of the disengagement of the descending inhibitory pain modulation system in fibromyalgia: an exploratory study. Issue 2 (May 2021) - Soldatelli, Matheus Dorigatti; Siepmann, Timo; Illigens, Ben Min-Woo; Souza dos Santos, Vinicius; Lucena da S Torres, Iraci; Fregni, Felipe; Caumo, Wolnei
Background: The main symptoms of fibromyalgia comprise diffuse pain, disability, depressive symptoms, catastrophizing, sleep disruption and fatigue, associated with dysfunction of the descending pain-modulating system (DPMS). Objectives: We aimed to identify patterns of main symptoms of fibromyalgia and neuroplasticity biomarkers (i.e. brain-derived neurotrophic factor (BDNF) and S100B protein) in non-responders to the conditioned pain modulation task (CPM-task) induced by immersion of hand in cold water (0–1°C). Furthermore, we evaluated if these patterns predict responsiveness to CPM-task. Methods: This cross-sectional study included 117 women with fibromyalgia (( n  = 60) non-responders and ( n  = 57) responders), with age ranging from 30 to 65 years old. We analysed changes in numerical pain scale (NPS-10) during the CPM-task using a standardized protocol. Results: A hierarchical multivariate logistic regression analysis was used to construct a propensity score-adjusted index to identify non-responders compared to responders to CPM-task. The following variables were retained in the models: analgesic use four or more times per week, heat pain threshold (HPT), poor sleep quality, pain catastrophizing, serum levels of BDNF, number of psychiatric diagnoses and the impact of symptoms of fibromyalgia on quality of life. Receiver operator characteristics (ROC) analysis showed non-responders can be discriminated from responders by a composite index of more frequent symptoms of fibromyalgia and neuroplasticity markers (area under the curve (AUC) = 0.83, sensitivity = 100% and specificity = 98%). Conclusion: Patterns of fibromyalgia symptoms and neuroplasticity markers may be helpful to predict responsiveness to the CPM-task which might help personalize treatment and thereby contribute to the care of patients with fibromyalgia.